Effects of Scalene Muscle Stretching on Slow Vital Capacity and Chest Expansion in Patients After Coronary Artery Bypass Grafting: An Interventional Study - Miral Vyas; Mihir Mehta; Falak Oza; Bhumika Ratnoo (Cardiovascular Innovations and Applications, 2024)
Background: Coronary artery bypass grafting (CABG) is a coronary revascularization technique associated with diminished pulmonary function. During the first week after CABG, slow vital capacity (SVC) decreases by 30%–60%. Scalene muscles affect pulmonary function because they attach to the 1 st and 2 nd ribs. Shorter scalene muscles can decrease inhalation volume and chest expansion. Very few studies have assessed the effects of scalene stretching on SVC and chest expansion in patients post-CABG. Therefore, this study was aimed at determining the effects of scalene muscle stretching on SVC and chest expansion in such patients. Methods: A total of 74 patients post-CABG (phase 2) meeting the inclusion criteria were randomly allocated to two groups: an intervention group (n = 30) performing scalene muscle stretching and a control group (n = 30) performing active neck exercise. Pre & Post SVC and chest expansion were measured in all patients. A total of 14 patients were excluded. Statistical analysis was conducted in SPSS software (version 20.0). Results: SVC showed significant increase (P < 0.05) in the intervention group compared with the control group. Chest expansion was statistically non-significant between groups (P > 0.05). Conclusion and clinical implications: Scalene muscle stretching improves SVC in patients post-CABG (phase 2). Hence, scalene stretching should be included in programs for improving respiratory function.